Synanceia quinque, a new species of stonefish (Synanceiidae) from Borneo and Flores - Mizuki Matsunuma; Bernardette Mabel Manjaji Matsumoto; Hiroyuki Motomura (Springer Verlag, 2022)
A new species of stonefish, Synanceia quinque (Synanceiidae) is described on the basis of two specimens (61.5–84.4 mm standard length) collected of Sabah (Borneo), Malaysia and Flores, Indonesia. The new species is characterized by 12 pectoral-fin rays, and is most similar to Synanceia alula Eschmeyer and Rama-Rao 1973 (11 pectoral-fin rays in the latter vs. 14 or more in other congeners). Other characters distinguishing S. quinque from S. alula include numbers of pelvic-fin rays [I, 5 in the former vs. I, 3 or 4 (usually I, 4) in the latter], gill rakers (0 + 4 or 5 vs. 0 or 1 + 7), and five preopercular spines/ skin faps (upper three spines relatively well developed, lower two rudimentary) (vs. four preopercle spines, fifth spine or skin fap absent). An updated key to species of Synanceia is provided.